Joint Genomic and Transcriptomic Analysis Reveals Candidate Genes Associated with Plumage Color Traits in Matahu Ducks - Pengwei Ren; Liu Yang; Muhammad Zahoor Khan; Yadi Jing; Meixia Zhang; Chao Qi; Xin Zhang; Xiang Liu; Zhansheng Liu; Shuer Zhang; Mingxia Zhu (Animals)
Plumage color is a key trait for identifying waterfowl breeds with significant economic importance. A white-feathered group has recently emerged within the native Matahu duck population, presenting an opportunity for breeding new lines. However, the genetic basis for this plumage variation is still unknown, necessitating further research. This study aims to identify the genetic mechanisms underlying the emergence of white-feathered individuals in the Matahu duck population through combined genome and transcriptome analysis, providing insights for selective breeding and the development of new white-feathered lines. In this study, a total of 1344 selected genes and 1406 significantly differentially expressed genes were identified through selection signal analysis and transcriptomic analysis, respectively. The functional enrichment of these genes revealed several key signaling pathways, including those related to cGMP-PKG, cAMP, PI3K-Akt, and MAPK. Furthermore, important candidate genes involved in melanin biosynthesis, such as MITF, MC1R, TYR, TYRP1, and ABCB6, were identified. Notably, 107 genes were detected by both methods, and, among these, DGKI, GPRC5B, HMX1, STS, ADGRA1, PRKAR2B, and HOXB9 are suggested to play a role in melanin formation and potentially influence plumage traits. Through the integrative approach combining genomic selection signals and transcriptomic analyses, we identified several candidate genes directly associated with plumage color, including MITF, TYR, TYRP1, and MC1R, along with multiple signaling pathways linked to melanin formation. We hypothesize that the expression of DGKI, GPRC5B, HMX1, STS, ADGRA1, PRKAR2B, and HOXB9, detected by both methods, may be closely related to the regulation of plumage color traits. These findings provide a foundational basis for further research aimed at elucidating the genetic mechanisms governing plumage color variation in ducks.